A research agenda for the restoration of tropical and subtropical grasslands and savannas - Buisson, Elise; Fidelis, Alessandra [UNESP]; Overbeck, Gerhard E.; Schmidt, Isabel B.; Durigan, Giselda; Young, Truman P.; Alvarado, Swanni T.; Arruda, André J.; Boisson, Sylvain; Bond, William; Coutinho, André; Kirkman, Kevin; et al. (Wiley, 2021)
Despite growing recognition of the conservation value of grassy biomes, our understanding of how to restore biodiverse tropical and subtropical grassy biomes (grasslands and savannas; TGB) remains limited. Several tools have recently been identified for TGB restoration, including prescribed fires, appropriate management of livestock and wild herbivores, tree cutting and shrub removal, invasive species control, and the reintroduction of native grasses and forbs via seeding or transplants. However, additional research for improved TGB restoration is needed. This article aims to identify ecological research priorities for TGB restoration. The following points are crucial to scale up TGB restoration and meet the challenges of the UN Restoration Decade. Research should focus on: disentangling the reasons why TGB are often undervalued and misunderstood; mapping TGB restoration opportunities; identifying regions where TGB and other biomes naturally exist as alternative stable states; recognizing areas with natural regeneration potential to avoid unnecessary intervention; restoring soil conditions; disentangling factors driving low seed quality, determining germination requirements and developing vegetative propagation techniques for TGB species; disentangling the limiting factors and key ecological processes underlying seedling establishment and community assembly; improving and validating long-term management to mimic natural disturbance regimes; setting the minimum attributes of desirable TGB in terms of structure, composition, functioning, and resilience; and improving monitoring of restoration outcomes. Such research has the potential to advance theory, policy, and practice in TGB restoration, ultimately resulting in long-term benefits for people and nature in some of the more neglected ecosystems of our planet.
Keywords: grasslands; grassy biomes; old-growth grasslands; savannas; tropical old-growth grassy biomes; woodlands